Mesas luso-brasileiras: alimentação, saúde & cultura. vol. II - Carmen Soares (DIAITA: Scripta & Realia, 2018)
The tendency of 21st century studies about the table has been to privilege as multi and transdisciplinary approaches. In fact, it is in its holistic sense that we use the term table, a universe that encompasses goods, people and ideas. Reflect today toward the table constitutes a process of careful inquiry into three of the main pillars of the man's relationship with food, throughout its history: food, health and culture. This book is the subject of Lusophone Tables and is organized in two volumes, containing five parts and a total of 25 chapters. The 13 chapters of the first volume focus on two central themes: food under the therapeutic and symbolic prism. In Part I (Therapeutic Tables: when food is medicine), it is evident that, historically, medical writings preceded the culinary literature. Part II (Sacred Tables: when food is a symbol) is referred to the table as answer and vehicle of dialogue with the transcendent.